2012
DOI: 10.1038/nrd3738
|View full text |Cite
|
Sign up to set email alerts
|

Are sirtuins viable targets for improving healthspan and lifespan?

Abstract: Although the increased lifespan of our populations illustrates the success of modern medicine, the risk of developing many diseases increases exponentially with old age. Caloric restriction is known to retard ageing and delay functional decline as well as the onset of disease in most organisms. Studies have implicated the sirtuins (SIRT1–SIRT7) as mediators of key effects of caloric restriction during ageing. Two unrelated molecules that have been shown to increase SIRT1 activity in some settings, resveratrol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
284
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(295 citation statements)
references
References 284 publications
(390 reference statements)
5
284
1
5
Order By: Relevance
“…We found that, in ob/ob mice, the SIRT1 level was lower in ECs recovered from both ischemic and nonischemic muscles of saline mice, while it increased upon a UnAG challenge. A number of SIRT1 targets have been described in mammals (44), and tumor suppressor p53 is included (38). Transcription factor p53 is involved in DNA damage mechanisms (45).…”
Section: Discussionmentioning
confidence: 99%
“…We found that, in ob/ob mice, the SIRT1 level was lower in ECs recovered from both ischemic and nonischemic muscles of saline mice, while it increased upon a UnAG challenge. A number of SIRT1 targets have been described in mammals (44), and tumor suppressor p53 is included (38). Transcription factor p53 is involved in DNA damage mechanisms (45).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps no compound has created greater debate on its effects on lifespan and health, on its precise mode of action and on its potential as a DR mimetic as the polyphenol resveratrol has (126)(127)(128) . Resveratrol has been shown to increased lifespan in yeast, C. elegans and Drosophila apparently through the activation of NAD-dependent histone deacetylases called sirtuins (129,130) , with SIRT1 activation reported to underlie the effects of DR in mammals (130) .…”
Section: Resveratrolmentioning
confidence: 99%
“…They have been implicated in diverse biological events, such as aging, energy control, circadian clocks, and mitochondrial biogenesis (Baur, Ungvari, Minor, Le Couteur, & de Cabo, 2012; Preyat & Leo, 2013; Wood et al., 2004). Of them, Sirt2 is associated with mitotic structures, beginning with the centrosome in mitotic prophase, the spindle in metaphase, and the midbody during cytokinesis, presumably to ensure normal cell division (North & Verdin, 2007).…”
Section: Introductionmentioning
confidence: 99%